The First Clinical and Functional Results of Myopia Correction Using a Solid-State Laser Unit - N. V. Maychuk; A. V. Tikhov; Kh. P. Takhchidi; N. Sh. Sarkhadov; I. S. Malyshev (Oftalʹmologiâ, 2023)
Relevance. Modern keratorefractive surgery (CRS) is a high-tech field of ophthalmology aimed at solving various problems of correcting a wide range of ametropias. Increasing the security of the RFI is one of the priority areas Purpose. To analyze the clinical and functional results of the use of the “Olimp™-2000” solid-state laser system during CRS using the method of superficial and sublamellar laser keratoablation and formulate recommendations for the therapeutic management of patients. Materials and methods. 53 patients (106 eyes) were examined, the average age was 28.5 ± 2.4 years. The inclusion criterion was moderate myopia and the absence of contraindications to CRC. If sufficient, taking into account safety criteria, CRS was performed by sublamellar keratoablation, if insufficient, superficial keratoablation was performed. In both cases, ablation was performed using a domestic solid-state laser machine. The observation period was 3 months. Pharmacological support in all cases was standard, adopted for the management of patients in FCMMG “YourMed”. Results. An analysis of the clinical and functional results of CRS using a solid-state laser device showed full compliance with the criteria set by the Food and Drug Administration (FDA). The accuracy of hitting the target refraction in the range of ± 0.5 diopters was 99.2 %; in 3 months of observation, no regression of the obtained refractive result was observed in any case. There was no loss of lines in any case, the BCVA after the operation corresponded to or exceeded by 1–2 lines the BCVA before the operation. When performing superficial keratoablation, in two cases, the loss of line 1 of the NCVA was noted due to the development of early subepithelial fibroplasia, which required correction of the pharmacological support. Conclusion. The analysis of the clinical and functional results of the correction of moderate myopia using the “Olimp™-2000” solid-state laser device showed high efficiency in terms of efficiency, safety, and predictability, despite little experience in using solid-state ablation in clinical practice. The use of Floas Mono® did not cause side effects in all cases and contributed to the smooth course of the early postoperative period. Thus, this drug is effective in the postoperative period and can be recommended for use in patients after CRC. The generation of ultraviolet radiation by modern solid-state devices for the purpose of correcting ametropia is a promising direction in CRS.